El deterioro del libro antiguo como fuente de información histórica - ASENCIO PADILLA, David; SÁNCHEZ HERRADOR, Miguel Ángel; CARRASCO PLEGUEZUELO, Inmaculada (Revista General de Información y Documentación, 2010)
Traditionally the deterioration of ancient books have been seen like a prejudice or like a decrease of their value, and often hurtful restorations which have been carried out, have involved an added damage and even they’ve tried to cover up, or better said, to fake books´ lost of hardware. However the deterioration itself, is a source of information about the life of each exemplary: utilization, abandonment, restoration, theft, pillaging, censorship, mutilation… facts that couldn’t be shown in another way. In addition, this information associated with others studies, as studies about handwritten notes, mark-reading, library catalogues, auctions, documents of file… would produce a more complete point of view about the history of each exemplary.